Chetolah, Ellis County - Wheeler, Jessica (Kansas State University, The Chapman Center for Rural Studies, 2012)
The lost town of Chetolah, located in Ellis County, Kansas, was settled by three diverse groups of people at different time intervals: the Pawnee Indians, optimistic railroad investors, and hopeful gold miners. The town struggled to survive after missing the railroad and finally drifted out of existence after being subjected to a false gold rush. Although the town was never completely revitalized, in the 1920s it became a tourist attraction known as Golden Springs Beach. This study provides a history of Chetolah using maps, newspapers, photographs, and an interview of the longtime property owner.
Jessica Wheeler, “Chetolah, Ellis County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/92.
Keywords: Ellis County; John C. Fremont; C.E. Foote; Chetolah; Fahrig Mining and Milling Company; Kansas Gold Field